2021
DOI: 10.21203/rs.3.rs-656824/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Educational Intervention on Promotion of Preventive Behavior of Knee Osteoarthritis in Women Over 40 Based on the Theory of Planned Behavior in Sample of Iranian Women

Abstract: Objectives. The purpose of this study was designed and conducted so that the educational intervention based on the theory of planned behavior be performed in order to promote preventive behaviors of knee osteoarthritis in women over 40 living in, Fars, I.R.IranMethods. This research is a quasi-experimental study. The subjects of the study were 100 women over the age of 40 who were under the coverage of Health Centers. The data collection tool was a questionnaire TPB. The educational intervention program consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…These results are consistent with Saffari, et al, observation that many OA patients experience stress due to their diminished mobility, increased disability, and diminished independence [35]. Those with RA are more likely to experience depressive symptoms, job loss, financial difficulties, social and relationship problems, and changes in relationship status [29]. The discomfort and limitations of osteoarthritis can also lead to depression and sleep problems.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with Saffari, et al, observation that many OA patients experience stress due to their diminished mobility, increased disability, and diminished independence [35]. Those with RA are more likely to experience depressive symptoms, job loss, financial difficulties, social and relationship problems, and changes in relationship status [29]. The discomfort and limitations of osteoarthritis can also lead to depression and sleep problems.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Jeihooni, et al, who noted that OA is the cause of a significant decline in physical activity came to the conclusion that physical exercise has numerous advantages for RA patients and ought to be widely practiced. A goal of therapeutic patient education for OA should be to encourage physical exercise [29]. The results of the current study indicated that the majority of the analyzed women experienced weariness, which is a physical consequence of OA.…”
Section: Discussionmentioning
confidence: 67%
“…This is might be explained by the effect of program intervention on improving preventive behaviors regarding osteoarthritis which increase awareness of studied women about preventive behaviors. This result was supported by Jeihooni, Fereidouni, Bahmandoost & Harsini, (2021) in Iran and found there was a significant difference between both groups in terms of the scores for attitude, subjective norms, perceived control behavior, preventive behavior before and after the intervention.…”
Section: Discussionsupporting
confidence: 64%
“…These results back up the claims made by Mirzaei, et al, that rheumatoid arthritis can impact the majority of the body's organs and raise the risk of mortality and morbidity [30]. In addition, Jeihooni, et al, came to the conclusion that physical exercise has many advantages for RA patients and should be widely adopted after recognising that OA is the cause of a noticeable decline in physical activity.…”
Section: Discussionsupporting
confidence: 62%